Integration of prices in major markets of onion and potato in India - SAHA, NANDINI; KAR, AMIT; JHA, GIRISH K; KUMAR, PRAMOD; VENKATESH, P; KUMAR, RAJEEV R (The Indian Journal of Agricultural Sciences, 2021)
Among the vegetable crops, onion and potato prices are more unstable due to seasonality of production, perishable nature, production uncertainty etc. Lack of information on potential market as well as arrival and price behaviour of onion and potato further worsen this situation of its growers. Since market integration helps in achieving price consistency and thus lead to marketing system efficiency, the present study explores market integration and price transmission during the period March 2009 to March 2019 across the wholesale markets using Johansen’s cointegration test and Granger Causality test. In this study to test the stationarity of the price series, Augmented Dickey Fuller test and Phillips-Perron test was used. The outcomes of the study strongly supported the presence of co-integration and interdependence of the selected markets from the result of Johansen cointegration test and Granger causality test revealed the presence of bidirectional relationship among most of the markets but also there exists unidirectional relationship among few markets.